Strategic modeling for future agriculture in Asia - Cenacchi, Nicola; Sulser, Timothy B. (Asian Productivity Organization, 2025)
This APO report pinpoints the declining agricultural productivity situation in APO economies since 2019 and explores how key measures could accelerate progress achieving food security and mitigating undernourishment by improving calorie availability per person. Key challenges include slowed agricultural productivity, climate change, land degradation, insufficient R&D investment, water scarcity, and inefficiencies in markets. The report examines measures such as policy interventions and investments in R&D, irrigation, and water use efficiency to enhance productivity, food security, and sustainable resource use. Such measures could accelerate progress toward achieving food security and mitigating undernourishment by improving calorie availability per person.